Insights into De Quervain’s Tenosynovitis as an Unintended Consequence of Problematic Smartphone Usage: A Cross-sectional Observational Study - Aswin Sugumaran; Dilip Kumar Naidu; Madhan Raju; Sabari Vaasan Lakshmikanthan; S Karthikeyan; Kevin Dhas; Vamsi Krishna; Praveen Raja (Journal of Clinical and Diagnostic Research)
Introduction: Smartphone use has been linked to Musculoskeletal Disorders (MSDs), particularly wrist and hand conditions like De Quervain’s Tenosynovitis (DQT), which causes inflammation of the tendons of the thumb, mainly the Abductor Pollicis Longus (APL) and Extensor Pollicis Brevis (EPB). In India, the rise in smartphone usage has led to a corresponding increase in such disorders. Aim: To investigate the association between problematic smartphone usage and the development of DQT and to assess its physical impact using the Visual Analogue Scale (VAS), Patient-rated Wrist/Hand Evaluation (PRWE) and quick Disabilities of the Arm, Shoulder and Hand (DASH) scores. Materials and Methods: A cross-sectional observational study was conducted at the Department of Orthopaedics, SRM Medical College Hospital and Research Centre, SRM Institute of Science and Technology, Chengalpattu, Tamil Nadu, India, from July 2024 to September 2024, with 300 participants aged 20-50 years. Participants were classified based on the results of Finkelstein’s Test and their smartphone usage patterns. Pain intensity was assessed using the VAS, while functional disability was measured using the quick DASH and PRWE questionnaires. Results: The DQT was more prevalent in younger individuals (20-30 years) and females, with prolonged smartphone use (>8 hours/day) and frequent horizontal screen orientation strongly linked to its occurrence. Specific hand gestures such as Horizontal screen Both Thumb-Both Hand Grip (HBT-BHG) were common in bilateral DQT, while Horizontal screen Unilateral thumb-Isolated Hand Grip (HUT-IHG) was more frequent in unilateral cases. Vertical screen Unilateral Index finger-Other Hand Grip (VUI-OHG) and Vertical screen Unilateral Thumb- Other Hand Grip (VUT-OHG) gestures showed a lower incidence of DQT. Group 1 experienced higher pain intensity (VAS score 5.43±1.34) and moderate disability scores (Quick DASH score 38.45±12.52; PRWE score 42.67±14.24), while Group 2 had minimal pain (VAS score 2.3±1.02) and minimal disability scores (Quick DASH score 11.96±6.68 and PRWE score 15.54±8.46). Conclusion: Problematic smartphone usage patterns (usage of phones for over 8 hours per day and horizontal screen orientation) were associated with the development of DQT, resulting in moderate disability scores that affected daily activities.